EFFECTIVE HEAT INSULATION OF COMPLICATED FORM FOR HEAT AGGREGATES OF METALLURGY - E. V. Toropov; D. N. Makarov; E. E. Toropov (Литьë и металлургия)
The matters of determination of rational parameters of isolation coverings for heat aggregates, functioning in metallurgical, machine-building and industrial complexes, are examined in the article. Recommendations on choice of geometrical parameters of isolation of complicated form, providing obtaining of energy saving effect at functioning of high-temperature aggregates, are offered.